Vegetative Phase Morphology Characterization of Local Rice From Paloh Distrit Sambas Regency - Finky, Asna Wati, Nur Arifin, Finky (Jurnal Sains Pertanian Equator, 2019)
Lokal rice is potential germplasm used as genetic source for assembly of better varieties in plant breeding programs. This research aims to obtain character information and genetic relationship vegetative phase of some local rice from Paloh District, Sambas Regency. This research was held in Danau Sentarum Street, Pontianak. This research used completely rendomized design (CRD) consisted of 7 treatments, that are V1 = Ringkak Barkat local rice, V2 = Ringkak Talok local rice, V3 = Mensere local rice, V4 = Ringkak Herman local rice, V5 = Siam Wangi local rice, V6 = Serawak local rice, V7 = Ringkak Ondot local rice. Each treatment was repeated 3 time and consisted of 10 samples. This research has been obtain 14 vegetative phase characters of local rice from Paloh District, Sambas Regency, that are seeding height, ligule shape, leaf surface, leaf attitude, flag leaf attitude, collar color, auricle color, leaf blade color, leaf sheath color, ligule color, leaf length, leaf width, childbearing, and plant height. The closest genetic relationship was Siam Wangi and Ringkak Barkat local rice with 100% similarity level, while the farthest genetic relationship was Ringkak Talok and Mensere lokal rice with 69,1% similarity level. keywords: characterization, genetic relationship, local rice